2021
DOI: 10.20524/aog.2021.0605
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of vessel plus surface classification system for the diagnosis of early gastric cancer after Helicobacter pylori eradication

Abstract: Background It has been reported that it is sometimes difficult to make a diagnosis of gastric cancer detected after Helicobacter pylori (H. pylori ) eradication. Therefore, we conducted a study to determine the usefulness of magnifying endoscopy using vessel plus surface classification system for making a diagnosis of early gastric cancer after H. pylori eradication. Method Usefulness of the markers of the vessel plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The rate of microsurface irregularity in MGC was significantly higher than that of microvascular irregularity, and microvascular irregularity was generally accompanied by microsurface irregularity. Both microsurface and microvascular irregularities could be valuable in diagnosing MGC, as in the large early gastric cancer 16,17 . In this study, there were two cases of regular microsurface and microvascular patterns.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The rate of microsurface irregularity in MGC was significantly higher than that of microvascular irregularity, and microvascular irregularity was generally accompanied by microsurface irregularity. Both microsurface and microvascular irregularities could be valuable in diagnosing MGC, as in the large early gastric cancer 16,17 . In this study, there were two cases of regular microsurface and microvascular patterns.…”
Section: Discussionmentioning
confidence: 70%
“…Both microsurface and microvascular irregularities could be valuable in diagnosing MGC, as in the large early gastric cancer. 16,17 Our study showed that the antrum is the most common affected site for MGC, followed by the angular incisures, which is also the most common site for large gastric cancer. 21,22 In other words, large gastric cancer may originate from MGC.…”
Section: Insignificant Endoscopic Manifestations and Missed Diagnosis Ofmentioning
confidence: 72%
“…Diffuse-type GC develops directly from highly active inflammation, whereas intestinal-type GC develops through destruction and replacement of tissues, such as atrophy and IM, and is termed Correa’s cascade[ 5 - 7 ]. GCs can also be described according to the different rates of incidence[ 8 , 9 ], lesion characteristics[ 10 - 12 ], and prognoses[ 13 - 16 ] as per the corresponding H. pylori infection status. In this editorial, we specifically describe the histological subtypes of GC and H. pylori infection status.…”
Section: Introductionmentioning
confidence: 99%